Teacher Training as a Strategy of Professional Development: Perceptions and Challenges - Rauteda, Khem Raj (Journal of NELTA Gandaki, 2023)
This article aimed to explore the beliefs and opinions of in-service secondary-level teachers towards teacher training for professional development. Moreover, it intended to identify major issues that existed in the field of teacher training in Nepal. It is a qualitative research study in which the teachers' stories and experiences have been documented. A purposive sampling strategy was used to select the sample from the target population. Unstructured in-depth interviews were conducted to collect data. The data were further analysed thematically. The study found that many teachers perceived teacher training as a strategy of professional development that equipped them with both the content and the pedagogical knowledge and skills. However, the study has highlighted various issues and challenges such as geographical difficulty, inaccessibility to the resources, centrality in training practices in the federal system, nepotism, favouritism, and political relations while selecting the trainees. The study implies that the training courses, provisions, policies, and programs are to be developed and launched based on the teachers’ needs. Furthermore, teacher training should be decentralised.